Attenuating the increased level of creatinine by N‐acetylcysteine: Raman spectroscopy and density functional theory‐based monitoring of in vitro complexation in aqueous solution. (1st May 2020) - Gangopadhyay, Debraj; Das, Moumita; Singh, Keshav Kumar; Singh, Ranjan K.; Tandon, Poonam
Abstract: The role of drug N ‐acetylcysteine (NAC) in preventing contrast‐induced nephropathy (CIN) and kidney diseases has been investigated with the help of in vitro Raman spectroscopy and density functional theory (DFT). Renal dysfunction or kidney failure is diagnosed by an increase in serum creatinine (CRN). The exposure to contrast agents during angiography also causes an increase in serum CRN, a condition termed as CIN. NAC is given to such patients, as it is known to prevent the toxic effect of CRN, although its mechanism of action is not clearly known till date. In the present study, we have studied the interaction between CRN and NAC and tried to detect the formation of a stable complex between the two by analyzing the in vitro Raman spectra of aqueous solutions of CRN and NAC mixed in different molar ratios. From the Raman spectral analysis, it is observed that a stable complex is formed at 1:1 molar ratio of CRN and NAC. This complex has been synthesized in the laboratory, and upon drying, it is transparent, gel‐like in appearance, and slightly yellowish in color. The complex is hygroscopic and has much better water solubility than CRN. Fourier‐transform infrared (FT‐IR) and Raman spectral analyses of the synthesized complex show the structural changes taking place because of complexation and provide proof that the complex is stable at room temperature. DFT‐based studies on a number of plausible structures of the complex have also been done to determine the most stable structure of the complex, and the mechanism of its formation has been explored by transition‐state calculations. This study highlights the effective role of NAC in reducing the toxic effect of CRN as the water‐soluble complex of CRN, and NAC is likely to be removed through urine. Abstract : The possibility of formation of a stable complex between N‐acetylcysteine and creatinine in 1:1 molar ratio in aqueous solution is observed by in vitro Raman spectral signatures.